Relationship of a six-second peak power cycle ergometer test with maximal and ballistic strength tests in international rugby union players - Rogers, T.; Gill, N.; Watkins, C.; Beaven, C. M. (International Journal of Strength and Conditioning, 2025)
The purpose of this study was to determine relationships between traditional tests of maximal and ballistic strength, with the results of a 6 s cycle sprint (6sCS) in international level Rugby Union (Rugby) players. Thirty-three international level male Rugby players participated in the study. Each player completed the 6sCS, sprint run, standing long jump, weighted and unweighted countermovement jumps, and a 1RM squat test. Pearson`s correlations were carried out to determine relationships between absolute (PPO) and relative peak power output (relPPO) from the 6sCS with the other tests of maximal and ballistic performance for the whole population and for positional groups. For the cohort, significant correlations (p=0.05) between relPPO and various measures of speed (r=0.63-0.73) and jump performance (r=0.48 to 0.53) were observed. In the Backs, there were large, significant relationships with weighted countermovement jump, standing long jumps, and 10 m sprint time (r=0.58 to 0.74). Large significant correlations were found with sprint and standing long jump performance in the Forwards (r=0.54 to 0.82). These significant correlations are most likely due to similarity in duration, energy system requirements, contraction types, and similarities in muscle groups recruited. Differences between position groups may reflect the physical qualities players possess to meet game demands. The study suggests that 6sCS may be a valuable addition to existing testing to evaluate maximal and ballistic intensity performancebenchmark levels of these physical capacities in elite RU players.